Bioregeneration Of Mono-Amine Modified Silica And Granular Activated Carbon Loaded With Mono-Azo Dyes In Batch Systems - Al-Amrani, Waheeba Ahmed Abdu (2013)
The objectives of this study were to investigate and compare the durations and efficiencies of bioregeneration of granular activated carbon (GAC) and mono-amine modified silica (MAMS) loaded with mono-azo dyes, namely Acid Orange 7 (AO7), Acid Yellow 9 (AY9) and Acid Red 14 (AR14) using sequential adsorption and biodegradation approach in batch systems. The bioregeneration efficiencies of GAC and MAMS loaded with each azo dye were quantified using the direct measurement of the azo dye content on the adsorbent by reloading the bioregenerated adsorbent. Additionally, some operational factors affecting the bioregeneration of azo dye-loaded MAMS, namely the presence/absence of co-substrate, acclimated/non-acclimated biomass, initial AO7 loading concentration, redox condition, type of acclimated biomass, initial AO7-acclimated biomass concentration, shaking speed, biomass acclimation concentration, and particle size were extensively investigated.